Answer:
2(3x+6) = 6x+12
3(2x-6) = 6x-18
6x+12=6x-18
Subtract 12 from 18, which gives you:
6x=6x-6
Subtract the 6x on the opposite side of the equal side, and your answer is: x = -6
Answer:
-2
Step-by-step explanation:
2x - 4 +2 - 2x
Combine like terms
2x-2x -4+2
0x -2
-2
Answer: linear
Step-by-step explanation: I'm not too sure if that's the answer
Answer:
A: 125%
Step-by-step explanation:
if thomas had walked his dog for 25 minutes today, and he walked an extra 5 minutes compared to yesterday, then that would mean he walked his dog 25% more than yesterday (yesterday being 100%) so therefore it would be 125%